Digitall Storytelling Untuk Meningkatkaln Karakter Siswa Sekolah Dasar Pada Kurikulum “Merdeka Belajar” - Anggita Nur Levitasari (BASICA, 2023)
This article aims to explain the effect of digital storytelling to improve the caliber of elementary school students in the “Freedom to learn” curriculum. The type of research used was a literature study that was conducted in advance. The collection of data was carried out by tracking journal articles through Google Scholar, Sinta, and other sources on the internet. Before digital storytelling was introduced, it was discovered that there was a significant backlog in the delivery of digital storytelling. After the use of digital storytelling, the results of the analysis of the results of the research conducted showed a positive and significant effect of the use of digital storytelling on the character improvement of elementary school students under the “Freedom of learning” curriculum. Digital storytelling contains character values, such as educational, social, moral, cultural, historical, and imaginative values that can help students' character. It can be concluded that digital storytelling has a significant impact on improving the caloric content of elementary school students, this hall is also one of the caloric content of the “Freedom of Learning” curriculum.